Inhibitory mechanism of Chinese herbal medicine extracts on Escherichia coli and its application to fermented-bag sausage. (April 2021) - Dang, Yali; Hao, Li; Li, Xiao; Sun, Yangying; Pan, Daodong; Wu, Zhen; Shen, Jiamin
Abstract: Since Chinese Herbal Medicine contain many antimicrobial chemicals, they have great potential as new antimicrobial agents. Five Chinese Herbal Medicine extracts were obtained from hawthorn leaf, ginkgo leaf, bamboo leaf, redskin peanut, and lotus leaf by thermal reflux. The optimal mixed ratio was 2: 2: 5: 9 (hawthorn leaf, ginkgo leaf, bamboo leaf, redskin peanut) using the orthogonal method. The minimum inhibitory concentration (MIC) was 1.3 mg/mL. The total flavonoid content in the mixed-plant extract was 21.5%, and the quercetin, vitexin, different vitexin, galangal and resveratrol content were 0.32, 4.38, 1.87, 0.36 and 1.35 mg/L, respectively. The inhibitory mechanism was studied by changes in growth curves, cellular structure, cell-wall permeability and cell-membrane integrity. Results showed that the addition of plant extracts reduced the presence of E. coli, while increasing AKP, conductivity and ion-channel enzymes. Plant extracts damaged E. coli cell-walls and cell-membrane structures. The addition of 6% mixed-plant extract showed a positive effect on the quality and safety of fermented-bag sausage. Highlights: The inhibition mechanism of plants on E. coli was investigated. The optimal mixed ratio of plant extracts was obtained using orthogonal method. The chemical properties and sensory quality of the fermented-bag sausage adding plant extracts were studied.